The development of social entrepreneur through family empowerment (Posdaya) in the Bogor City - Ratno Ratno; Adri Wihananto; Syarief Gerald Prasetya (STIE Binaniaga, 2020)
Unemployment in urban areas is a social problem that must be resolved immediately. One way to overcome these social problems is community empowerment through social entrepreneurship or better known as social entrepreneur. The purpose of this research is to provide input in policy making related to handling economic and social problems and also as a medium for increasing knowledge as well as a reference source for further research related to Posdaya. The research method uses Qualitative Interactive analysis, namely the process of searching, compiling and analyzing data obtained from interviews in a systematic manner so that it is easy to understand and of course can be informed to others. Research results: the characteristics of Posdaya cadres in Bogor City based on individual characteristics are mostly female, aged 25 to 45 years, have the highest education equivalent to SMU (Senior High School), work as entrepreneurs and have been administrators for 4 to 6 years. In a qualitative analysis, it is found that sociopreuner and social innovation have a relationship with the success of the Posdaya (Social Entrepreneur), where sociopreneurs and social innovation tend to have a positive relationship with Social Entrepreneurs.Keywords: Social Entrepreneur and Family Empowerment